2007
DOI: 10.1002/bjs.5705
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of effect of synbiotics, neomycin and mechanical bowel preparation on intestinal barrier function in patients undergoing colectomy

Abstract: The combination of MBP, neomycin and synbiotics reduces the prevalence of faecal Enterobacteriaceae and bacterial translocation; however, this was not associated with a reduction in inflammatory response or septic morbidity in this study. Larger trials are needed before a change in practice can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
115
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 28 publications
(44 reference statements)
2
115
1
4
Order By: Relevance
“…From the remaining 11 RCTs, three were excluded: one article was a letter to the editor concerning an already published RCT, one focused on the combination of preoperative and postoperative use of probiotics versus postoperative use of probiotics [17], and one was an animal study. Thus, nine RCTs ultimately qualified for inclusion in our study [18][19][20][21][22][23][24][25][26].…”
Section: Evidence From Rctsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the remaining 11 RCTs, three were excluded: one article was a letter to the editor concerning an already published RCT, one focused on the combination of preoperative and postoperative use of probiotics versus postoperative use of probiotics [17], and one was an animal study. Thus, nine RCTs ultimately qualified for inclusion in our study [18][19][20][21][22][23][24][25][26].…”
Section: Evidence From Rctsmentioning
confidence: 99%
“…Six studies [18][19][20][21][22][23] used the combination of various bacterial species in the probiotic supplement, while three studies [24][25][26] used only one type of bacterial species. Four studies [18,20,23,24] did not provide any data regarding the exact follow-up of patients following surgery, while four studies [19,21,22,26] reported that patients were observed for 30 days after surgery and one study [25] observed patients for at least 3 months after surgery. In two studies [22,23], patients did not receive antibiotics for at least 1 month before surgery, while in one study [26] the patients were not administered antibiotics for at least 1 week before surgery; six studies [18-21, 24, 25] did not provide any data regarding the administration of antibiotics in patients prior to surgery.…”
Section: Evidence From Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several randomized controlled trials, including pancreatoduodenectomy, hepatobiliary resection and liver transplantation, demonstrate that the use of probiotics in patients undergoing abdominal surgery is a promising approach to the prevention of post-operative infectious complications [8][9][10][11]. Nevertheless, the effectiveness of probiotics treatment for prevention of infectious complications after colorectal surgery remains inconclusive [1,3,[12][13][14][15][16][17][18][19][20][21], possibly due to differences in patient groups, varying preparations of probiotics, and heterogeneity in the quality of methods. Whether or not beneficial bacteria actually survive in the intestine also remains unclear.…”
mentioning
confidence: 99%